Learning to unlearn for transformative learning, an Epistemological look - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2021)
This paper corresponds to a reflection on various theories and approaches to learning and their relevance in the training of social agents, a reflection that emerges from the practice of training, and taking into account the fact that the meaning of what learning implies and how it is You learn is not at the center of the discussion in Latin American universities, in which what is taught is more emphasized than how to teach.